A facile reduction of aromatic nitro compounds to aromatic amines with bis(cyclopentadienyl)titanium(IV) dichloride-indium system - Yoo, BW; Lee, SJ; Yoo, BS; Choi, KI; Kim, JH (TAYLOR & FRANCIS INC, 2002)
Cp2TiCl2/In system was found to be a new reagent for reducing various aromatic nitro compounds to the corresponding aromatic amines in good yields under mild and neutral conditions.
Keywords: ANILINES